Caveatable interest in Malaysia / Fadzilah Omar - Omar, Fadzilah (Faculty of Law, 1986)
The provision for lodging caveat is for the purpose of enabling parties to protect interests which, owing to a defect in the instrument or want of form or otherwise, they cannot protect by the ordinary process of registration. Caveat may be entered by the Registrar and by application of third parties. However, this project paper will stress more on caveat entered by application of third parties.